2010
DOI: 10.1371/journal.pone.0015618
|View full text |Cite|
|
Sign up to set email alerts
|

Constitutive Overexpression of Muscarinic Receptors Leads to Vagal Hyperreactivity

Abstract: BackgroundAlterations in muscarinic receptor expression and acetylcholinesterase (AchE) activity have been observed in tissues from Sudden Infant Death Syndrome (SIDS). Vagal overactivity has been proposed as a possible cause of SIDS as well as of vasovagal syncopes. The aim of the present study was to seek whether muscarinic receptor overexpression may be the underlying mechanism of vagal hyperreactivity. Rabbits with marked vagal pauses following injection of phenylephrine were selected and crossed to obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…The detailed mechanisms by which the responsiveness of the cholinergic antiinflammatory pathway is regulated remain unclear. Recent evidence suggests that vagal reactivity and cholinesterase activity depend on the constitutive expression of acetylcholine receptors at the peripheral organs …”
Section: Discussionmentioning
confidence: 99%
“…The detailed mechanisms by which the responsiveness of the cholinergic antiinflammatory pathway is regulated remain unclear. Recent evidence suggests that vagal reactivity and cholinesterase activity depend on the constitutive expression of acetylcholine receptors at the peripheral organs …”
Section: Discussionmentioning
confidence: 99%
“…Compared with controls, SIDS cases showed an increase in both the density of cardiac muscarinic receptors and the erythrocyte acetylcholinesterase enzyme activity. A subsequent study demonstrated that the cardiac muscarinic receptor overexpression plays a critical role in the development of vagal hyperreactivity, whereas the acetylcholinesterase hyperactivity appears as a compensatory consequence of it [65]. …”
Section: Sudden Infant Death Syndromementioning
confidence: 99%
“…The measurement of acetylcholine in real time is neither easy nor reliable. Thus, we tested the hypothesis of muscarinic receptor overexpression, first in an experimental model of vagal hyperactivity [11] and an abnormally high muscarinic receptor density was observed in the myocardium of rabbits presenting VO [11,12]. We have observed a good correlation between the muscarinic receptor density and the ECG R-R intervals, i .…”
Section: Introductionmentioning
confidence: 99%
“…This observation concerned the M 2 and M 3 subtypes of muscarinic receptors expressed in the heart of rabbits. But it was for the M 2 receptors (M 2 R) that the correlation was the best [12]. For the rest of our exploratory work in this area, we focused on the M 2 subtype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation